Gold Nanoclusters for NIR‐II Fluorescence Imaging of Bones - Li, Deling; Liu, Qiang; Qi, Qingrong; Shi, Hui; Hsu, En‐Chi; Chen, Weiyu; Yuan, Wenli; Wu, Yifan; Lin, Sien; Zeng, Yitian; Xiao, Zunyu; Xu, Lingyun; et al. (Small (Weinheim an der Bergstrasse, Germany), 2020)
Fluorescence imaging in the second near‐infrared window (NIR‐II, 1000–1700 nm) holds great promise for deep tissue visualization. Development of novel clinical translatable NIR‐II probes is crucial for realizing the medical applications of NIR‐II fluorescence imaging. Herein, the glutathione‐capped gold nanoclusters (AuNCs, specifically Au25(SG)18) demonstrate highly efficient binding capability to hydroxyapatite in vitro for the first time. Further in vivo NIR‐II fluorescence imaging of AuNCs indicate that they accumulate in bone tissues with high contrast and signal‐background ratio. AuNCs are also mainly and quickly excreted from body through renal system, showing excellent ribs and thoracic vertebra imaging because of no background signal in liver and spleen. The deep tissue penetration capability and high resolution of AuNCs in NIR‐II imaging render their great potential for fluorescence‐guided surgery like spinal pedicle screw implantation. Overall, AuNCs are highly promising and clinical translatable NIR‐II imaging probe for visualizing bone and bone related abnormalities. The glutathione‐capped gold nanoclusters, Au25(SG)18, demonstrate highly efficient binding capability to hydroxyapatite for the first time. They can be utilized for bone imaging with NIR‐II fluorescence with high contrast and can be excreted through renal system. The deep tissue penetration capability and high resolution render their great potential for clinical translation.